Mediterranean Paradiplomacies : the Dynamics of Diplomatic Reterritorialization. - Duran, Manuel (Diplomatic studies., 2015)
In 'Mediterranean paradiplomacies: The dynamics of diplomatic reterritorialization', Manuel Duran presents a new view on the phenomenon of paradiplomacy by analyzing the diplomatic activities of a number of Mediterranean substate entities as a site of political territorialization. The international agency of these substate entities is giving way to new patterns of territorialization, as well as alternative forms of diplomacy.00Duran examines the diplomatic activities of two Spanish, two French and two Italian regions. The book poses the question of why and how these regions operate diplomatically in a given territorial milieu and convincingly elucidates the particular patterns of reterritorialization that result from these diplomatic activities.